The Death of God in Culture: theoretical aspects on the Desecration of the Sacred in Postmodernity - Felipe Zacarias, William; Renato Westphal, Euler (Vox Scripturae - Revista Teológica Internacional, 2025)
There is an intrinsic relationship between the West and the Judeo-Christian worldview (weltanschauung). The secularization of protestantism in the West enjoys the material benefits of christianity without, however, taking into account the very immateriality of the Christian phenomenon. Thereby secularization is the own vocation of the Christian faith that continually empties himself and fulfills his vocation (Berufung) in the world through his profession (Beruf). Postmodernity breaks with everything that resembles Christianity: human dignity, the beauty of art, and the notion of history. With this, it returns to the dionysiac era of chaos, materiality and hedonism. The God of the cross confounds the powers of the immanent world, because God shed his blood so that human blood would be spared from being shed. Therefore, what is the relevance of the disgusting God of the cross to postmodernity? How has it been reinterpreted as madness? Without eschatology, are there criteria in an eternal return of it? How far is the vattminian Kénosis valid? More than answers, it is proposed a reflection on contemporaneity and its implications in culture.
Keywords: Postmodernity; Culture; Sacred; Secularization; Religious Heritage